К проблеме сопоставительного описания словообразования наречий словенского и русского языков - Михайловна Коницкая, Елена (Slavistica Vilnensis, 2002)
This article discusses word-formation issues concerning adverbs in two Slavonic languages. As a Slovenian theory of synchronic formation has not fully developed because of problems in interpreting constructions such as slej ko prej, kratko malo, and etymologically prepositional constructions, the paper proposes using a word-formation theory developed for Russian as a theoretical basis of comparing Russian and Slovenian adverbs.Based on material from the Russian Grammar and the Dictionary of Slovenian Literary Language, the article compares a) relationships between productive and derivative stems, and b) word-formation for adjectival adverbs.The paper also discusses the considerable range of formal means for expressing various morphological meanings in Russian compared with the situation in Slovenian.